Synthesis of Polydispersed P(St-MMA-AA) Microspheres and Fabrication of Colloidal Crystals with Non-Compact Morphology - Ifijen, Ikhazuagbe H.; Jonathan, Eribe M.; Jacob, Jacob N.; Udokpoh, Nyaknno U.; Archibong, Ukeme D. (Tanzania Journal of Science, 2022)
Great attention has been given to the synthesis of monodispersed and uniform colloidal polymer particles with controllable particle sizes. However, investigations on the preparation, characterization and fabrication of polydisperse polymeric particles are very few. Polydisperse polymers are also needed to meet the new demands of the modern markets due to the ease of their synthesis. This study, therefore, synthesized polydispersed poly(styrene-methyl-methacrylate acrylic-acid) (P(St-MMA-AA)) via emulsion polymerization synthetic approach under unstable reaction conditions. The synthesized P(St-MMA-AA) microparticles were characterized using Fourier transform infrared spectroscopy (FTIR), dynamic light scattering (DLS), a thermo-gravimetric analyzer (TGA) and scanning electron microscope (SEM). The DLS results revealed a highly polydispersed P(St-MMA-AA) microparticles with an average particle diameter of 803.4 nm. SEM, TEM (transmission electron microscopy) and AFM (atomic force microscopy) analyses showed that the particles were spherical and polydispersed. The unequal diameters and non-compact nature of the fabricated colloidal crystals may have affected its possible uses in some specific applications such as decorative coatings, biomedical and sensing applications. However, other materials can be incorporated into the polydispersed prepared P(St-MMA-AA) colloidal microspheres to improve their properties and possible applications. Keywords: Emulsion polymerization; Polydispersed; Polymer; P(St-MMA-AA)